A nanofiber-based multifunctional hydrogel and its preparation method and application in drug delivery
Through the design of nanofiber-based multifunctional hydrogel, the problem of detecting trivalent ion and butyryl cholinesterase activity in serum and low load efficiency of traditional hydrogel systems is solved, and the Fe3+ and butyryl choline are achieved Sensitive detection of esterase activity and efficient loading of anti-cancer drugs have improved the efficiency of tumor treatment and drug sustained release characteristics.
Patent Information
- Application Number
- CN202211457481.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-21
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-11-21
AI Technical Summary
The prior art has problems of complex procedures, time-consuming and high cost when detecting trivalent ions and butyryl cholinesterase activities in serum. At the same time, the traditional hydrogel system is inefficient in loading anti-cancer drugs and photothermal agents. It is difficult to meet the needs of tumor treatment.
Using nanofiber-based multifunctional hydrogel, high-density amino and phenolic hydroxyl groups were introduced by carboxylated nanocellulose fiber surface to prepare phenolic hydroxyl-rich nanofiber-based detection materials to achieve selective detection of Fe3+ and butyryl choline Recursive detection of esterase activity, and the near-infrared responsive Prussian blue nanoparticles are generated during the detection process, which improves the photothermal conversion efficiency and mixes them with tumor treatment drugs, water-soluble chitosan and sodium alginate to form Multifunctional hydrogel.
Sensitive detection of Fe3+ and butyrylcholinesterase activities is achieved, the load capacity of anti-cancer drugs and photothermal agents is improved, the efficiency of tumor treatment and the sustained release characteristics of the drug are enhanced, and the utilization rate of materials is improved.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomass fiber modification, and in particular relates to a nanofiber-based multifunctional hydrogel and a preparation method thereof and application thereof in drug delivery. Background Art
[0002] Abnormal changes in the activity of related enzymes and the content of metal ions in the blood can cause cancer.
[0003] Excessive trivalent iron ions in the blood can cause lipid peroxidation, thereby causing an imbalance between the human oxidative system and the antioxidant system, thereby damaging DNA and causing cancer. The traditional trivalent iron ion detection method is complicated, time-consuming, costly, and highly professional, which seriously hinders its practical application. In recent years, many new methods have been developed, among which the solid-based functional colorimetric detection method is simple, easy to carry, visible color changes, effective on-site identification of heavy metals, and easy to recycle. In addition to trivalent iron ions, too low activity of butyrylcholinesterase in serum can also cause cancer and other diseases. However, the traditional method for detecting butyrylcholinesterase activity is complicated, time-consuming, costly, and requires strong professional operation. The photothermal effect instant detection platform has become a new diagnostic technology for testing butyrylcholinesterase activity because of its high sensitivity, reliability, simplicity, and low cost. The concentration of trivalent iron ions in serum and the sensitivity of butyrylcholinesterase activity are closely related to the specific functional group density corresponding to the material.
[0004] Research on cancer cannot just stay at the level of detection, and then focus on the treatment of tumor tissue. Chemotherapy is usually used to treat cancer in clinical practice, but it has toxic side effects, low treatment efficiency and uncontrollable treatment. Injectable hydrogels are a strategy to improve these problems. Injectable hydrogels are suitable for drug delivery because of their porous structure, high water absorption (usually 70–99%) similar to human tissue, and the adjustability of their mechanical and flow properties, which endow them with drug biocompatibility and encapsulation potential. Hydrogels can form a drug elution reservoir to slowly release drug molecules while maintaining high local concentrations for a long time. However, single-mode treatment methods are far from meeting the treatment of tumors. Photothermal therapy has been a research hotspot in recent years. Photothermal therapy is to inject materials with high photothermal conversion efficiency into tumor tissue and apply an external light source (usually near-infrared radiation). Because only at a specific laser irradiation time and position will there be a photothermal conversion effect, the resulting high temperature can achieve dual control of cancer cell killing time and space. Secondly, local heat will improve cell metabolism and cell membrane permeability, and light radiation will promote the absorption of anticancer drugs. However, conventional hydrogel systems have low efficiency in loading anticancer drugs and photothermal agents.
[0005] Therefore, it is urgent to find a carrier substrate that can not only improve the sensitivity of detecting the concentration of trivalent iron ions and the activity of butyrylcholinesterase in serum, but also enhance the loading capacity of hydrogels for anticancer drugs and photothermal agents.
[0006] Nanocellulose fibers are abundant in source, low in cost, contain a large number of easily modifiable groups, surface charge, high porosity, and high specific surface area that is conducive to the adsorption and collection of heavy metal ions and active molecules. In addition, nanocellulose fibers have excellent biocompatibility and can interweave to form nanocages and 3D network structures to better and more immobilize anticancer drugs and photothermal agents. Summary of the invention
[0007] The purpose of the present invention is to provide a nanofiber-based multifunctional hydrogel and a preparation method thereof, wherein the material obtained during the preparation process has 3+ Concentration-specific detection, recursive detection of butyrylcholinesterase activity, anticancer drug delivery, and tumor therapeutic performance.
[0008] The above-mentioned purpose of the present invention is achieved by the following technical solutions:
[0009] A nanofiber-based multifunctional hydrogel is based on carboxylated nanocellulose fibers, on the surface of which high-density amino groups and phenolic hydroxyl groups are introduced to prepare a selective Fe 3+ The phenolic hydroxyl-rich nanofiber-based detection material is used to detect Fe 3+ At the same time, enrichment of Fe 3+ On the surface of a phenolic hydroxyl-rich nanofiber-based detection material, a recursive nanofiber-based detection material that can further detect butyrylcholinesterase is prepared in situ, and in the process of detecting the activity of butyrylcholinesterase, Prussian blue nanoparticles with near-infrared response performance are generated in situ on the surface of the recursive nanofiber-based detection material to prepare a nanofiber-based photothermal effect material with near-infrared response, which is then mixed with tumor therapeutic drugs, water-soluble chitosan and sodium alginate to form a nanofiber-based multifunctional hydrogel;
[0010] The phenolic hydroxyl-rich nanofiber-based detection material is prepared by grafting polyethyleneimine onto the surface of carboxylated nanocellulose fibers, and then further grafting gallic acid.
[0011] The carboxylated nanocellulose fibers are prepared by oxidizing biomass pulp fibers through sodium periodate oxidation and TEMPO / NaBr / NaClO oxidation system, and the carboxylated nanocellulose fibers have a large number of carboxyl groups.
[0012] The biomass pulp fiber is bleached pulp fiber, and the bleached pulp fiber is a mixture of one or more of bleached bagasse pulp fiber, bleached coniferous wood pulp fiber and bleached broadleaf wood pulp fiber.
[0013] The present invention provides a method for preparing a nanofiber-based multifunctional hydrogel, comprising the following steps:
[0014] S1. Preparation of carboxylated nanocellulose fibers: using sodium periodate to selectively oxidize the hydroxyl groups on C2 and C3 of the cellulose structural units of biomass pulp fibers into aldehyde groups to prepare dialdehyde fibers; then using a TEMPO / NaBr / NaClO oxidation system to oxidize the aldehyde groups on C2 and C3 and the hydroxyl groups on C6 of the cellulose structural units of the dialdehyde fibers into carboxyl groups, and controlling the degree of oxidation by controlling the reaction conditions to prepare carboxylated nanocellulose fibers; the biomass pulp fibers are bleached pulp fibers, and the bleached pulp fibers are a mixture of one or more of bleached bagasse pulp fibers, bleached coniferous wood pulp fibers, and bleached broadleaf wood pulp fibers.
[0015] S2. Preparation of phenolic hydroxyl-rich nanofiber-based detection materials: Using carboxylated nanocellulose fibers as a matrix, polyethyleneimine was introduced through an amidation reaction to prepare amino-modified nanocellulose fibers, and then the amino groups were reacted with the carboxyl groups of gallic acid to introduce phenolic hydroxyl groups to prepare phenolic hydroxyl-rich nanofiber-based detection materials;
[0016] S3. Preparation of recursive nanofiber-based detection materials: Detection of Fe using phenolic hydroxyl-rich nanofiber-based detection materials 3+ , to achieve low concentration Fe 3+ Selective detection of Fe 3+ The phenolic hydroxyl-rich nanofiber-based detection material is enriched on its surface, and a recursive nanofiber-based detection material is prepared in situ, which can further detect butyrylcholinesterase;
[0017] S4. Preparation of near-infrared responsive nanofiber-based photothermal effect materials: Using thiocholine iodide, the enzymatic hydrolysis product of butyrylcholinesterase, thiocholine, enriched on the surface of the recursive nanofiber-based detection material, 3+ Reduction to Fe 2+ , and then react with potassium ferrocyanide solution under acidic conditions to in-situ generate Prussian blue nanoparticles on the surface of the recursive nanofiber-based detection material. The Prussian blue nanoparticles have high absorption in the near-infrared light region, thereby obtaining a nanofiber-based photothermal effect material with near-infrared response;
[0018] S5. Preparation of nanofiber-based multifunctional hydrogel: Near-infrared responsive nanofiber-based photothermal effect materials, tumor therapeutic drugs, and water-soluble chitosan are uniformly dispersed in water, and then sodium alginate is added under stirring at room temperature to form a nanofiber-based multifunctional hydrogel.
[0019] Specifically, the preparation of carboxylated nanocellulose fibers in step S1 is specifically performed as follows: adding biomass pulp fibers to water, stirring thoroughly until cellulose is evenly dispersed in the water, adding TEMPO and NaBr in order, and then adding NaClO, stirring at room temperature, adjusting the pH of the reaction system to 10 with NaOH, until the pH value of the reaction system remains unchanged, which is the end point of the reaction, adding anhydrous ethanol to terminate the reaction, centrifuging the product, washing until the supernatant is neutral, and freeze-drying. The obtained product is carboxylated nanocellulose fibers with a carboxyl content of 1.4 mmol / g; the addition ratio of the biomass pulp fibers, TEMPO, NaBr, and NaClO is 2.0-8.0 g: 0.032-0.128 g: 2.0-8.0 g: 3.55-14.20 mL; the corresponding TEMPO concentration is 0.1-0.4 mmol / g, the NaBr concentration is 1-4 mmol / g, and the NaClO concentration is 6-24 mmol / g.
[0020] Specifically, the preparation of the phenolic hydroxyl-rich nanofiber-based detection material in step S2 is specifically performed as follows: water is added to the carboxylated nanocellulose fiber, ultrasonically dispersed to make it uniform, and then 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are added in sequence, and then polyethyleneimine is added, mixed evenly, and stirred at room temperature for reaction. After the reaction is completed, the product is centrifuged, the supernatant is removed, and the precipitate is repeatedly washed with deionized water until the washing liquid is neutral. The obtained product is amino-modified nanocellulose fiber; the obtained amino-modified nanocellulose fiber is mixed with water, ultrasonically dispersed to make it uniform, and then gallic acid is added, and then 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are added in sequence, mixed evenly, and stirred at room temperature for reaction. After the reaction is completed, the product is centrifuged, the supernatant is removed, and the precipitate is repeatedly washed with deionized water until the washing liquid is neutral. The obtained product is a phenolic hydroxyl-rich nanofiber-based detection material, which has a high sensitivity to Fe 3+ The minimum detection limit can be as low as 10 -10 mol / L, achieving the goal of Fe 3+ Trace detection; the added amount ratio of the carboxylated nanocellulose fiber, polyethyleneimine, and gallic acid is 1.0-5.0g:2.0-10.0g:1.0-5.0g.
[0021] Specifically, the preparation of the recursive nanofiber-based detection material in step S3 is specifically performed as follows: the phenolic hydroxyl-rich nanofiber-based detection material is uniformly dispersed in water to prepare a 0.1 mg / mL phenolic hydroxyl-rich nanofiber-based detection material stock solution, and the phenolic hydroxyl-rich nanofiber-based detection material stock solution and different concentrations of Fe 3+After the aqueous solutions were mixed in a volume ratio of 1:5 to 5:1, the ultraviolet absorption intensity of the mixed solution at 196 nm was tested at room temperature, and the Fe 3+ The enrichment amount was used to prepare the recursive nanofiber-based detection material in situ, which can further detect butyrylcholinesterase and control different Fe 3+ The concentration of aqueous solution can regulate the Fe on the surface of phenolic hydroxyl-rich nanofiber-based detection materials 3+ The enrichment amount can be adjusted to adjust the detection limit of butyrylcholinesterase.
[0022] Specifically, the preparation of the near-infrared responsive nanofiber-based photothermal effect material in step S4 is specifically performed as follows: 20 to 40 μL of a 50 to 100 mmol / L substrate iodide butylthiocholine iodide BuTCh solution is added to 20 to 40 μL of a 4000 to 16000 mmol / L solution in a 96-well plate. –1 The samples were incubated at 37°C for 30 min in a butyrylcholinesterase BuChE solution, then 0.01-0.02 g of recursive nanofiber-based detection material was added, and then incubated for another 10 min. Finally, 20-40 μL of 5-10 mmol / L K 3 [Fe(CN) 6 ] solution and 60-120 μL of 10-20 mmol / L acetic acid-sodium acetate buffer were mixed evenly with the solution in the well plate and incubated for 15 min. Prussian blue nanoparticles were in situ generated on the surface of the recursive nanofiber-based detection material to prepare a near-infrared responsive nanofiber-based photothermal effect material. The material was irradiated with 808 nm near-infrared laser for 3 min, and then the temperature change was recorded. The activity of butyrylcholinesterase was determined by the temperature change. The higher the near-infrared response temperature, the higher the butyrylcholinesterase activity.
[0023] Specifically, the preparation of the nanofiber-based multifunctional hydrogel in step S5 is as follows: uniformly dispersing the near-infrared responsive nanofiber-based photothermal effect material, tumor therapeutic drug and water-soluble chitosan in water, and then adding sodium alginate under stirring at room temperature to obtain the nanofiber-based multifunctional hydrogel; wherein the mass percentages of the near-infrared responsive nanofiber-based photothermal effect material, water-soluble chitosan, sodium alginate and tumor therapeutic drug in the hydrogel are 0.1-1 wt%, 0.1-2wt%, 0.001-0.01wt% and 0.05-1wt% respectively; the tumor therapeutic drug is a mixture of one or more of doxorubicin, curcumin, moxifloxacin, vemurafenib and camptothecin.
[0024] The phenolic hydroxyl-rich nanofiber-based detection material can be used to detect Fe 3+ Concentration, Fe 3+The minimum detection limit is as low as 10 -10 mol / L.
[0025] The recursive nanofiber-based detection material can be used for recursive detection of butyrylcholinesterase activity, and the detection limit of butyrylcholinesterase activity is 5000 to 15000 UL. -1 (Included in the normal human activity range of 6900 to 11000 UL –1 When the recursive nanofiber-based detection material is used to detect the activity of butyrylcholinesterase, the enzymatic hydrolysis product of butyrylcholinesterase of iodinated butyrylthiocholine iodide, thiocholine, is used to enrich the Fe 3+ Reduction to Fe 2+ , and then react with potassium ferrocyanide solution under acidic conditions to generate Prussian blue nanoparticles in situ on the surface of the recursive nanofiber-based detection material. Prussian blue nanoparticles have high absorption in the near-infrared light region. 808nm near-infrared laser irradiation is used to achieve temperature changes, and the activity of butyrylcholinesterase is judged by temperature changes.
[0026] The nanofiber-based multifunctional hydrogel can be used for anticancer drug delivery and tumor treatment. The drug loading of the hydrogel is controllable and the maximum drug loading can reach 600 mg / g. The drug sustained release rate within 24 hours is 50%, and the drug sustained release rate within 48 hours is 95%. It can be prepared into injectable hydrogels and hydrogels for wound treatment. The controlled release of drugs can be achieved through near-infrared response, thereby realizing photothermal chemotherapy of tumors in vivo and in vitro.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The nanocellulose fiber-based multifunctional material prepared by the present invention is effective in detecting Fe 3+ After that, the activity of butyrylcholinesterase can be generated and recursively tested. After testing the activity of butyrylcholinesterase, materials with near-infrared photothermal conversion are further generated and applied to photothermal therapy of tumors. At the same time, it has excellent anticancer drug loading capacity, giving the material chemotherapeutic properties. The progressive multi-level utilization mechanism of this material greatly improves the utilization rate of the material.
[0029] (2) The present invention grafts polyethyleneimine with a high amino density onto carboxylated nanocellulose fibers, which is carried out by the amidation reaction of the carboxyl groups of the nanocellulose fibers and the amino groups of the polyethyleneimine. At the same time, the phenolic hydroxyl group is introduced by utilizing the amino groups of the nanocellulose fibers to react with the carboxyl groups of gallic acid. Therefore, the degree of reaction of the amino groups of the polyethyleneimine in the present invention is to regulate the detection of Fe 3+ The key to sensitivity and detection limit is to adjust the amount of gallic acid added, which is the key to the detection limit of butyrylcholinesterase.
[0030] (3) The present invention utilizes the unique chemical and physical properties of nanocellulose fibers to ingeniously endow anti-tumor drug carriers with near-infrared photothermal properties, thereby achieving coordinated killing of tumors by photothermal therapy while having a high anti-tumor drug capacity to improve the efficiency of chemotherapy. DETAILED DESCRIPTION
[0031] Example 1
[0032] S1. Preparation of carboxylated nanocellulose fibers: Add 2.0g of bleached bagasse pulp fibers (absolutely dry pulp) to 200mL of deionized water and stir thoroughly until the cellulose is evenly dispersed in the water. Add 0.032g of TEMPO (0.1mmol / g), 2.0g of NaBr (1mmol / g), and then add 3.55mL of NaClO (6mmol / g) in sequence. Then stir magnetically at room temperature for 4h, adjust the pH of the reaction system to 10 with 0.5M NaOH, until the pH value of the reaction system remains unchanged, which is the end point of the reaction. Add 5mL of anhydrous ethanol to terminate the reaction. Centrifuge the product, wash it repeatedly with distilled water until the supernatant is neutral, freeze-dry it, and the resulting product is carboxylated nanocellulose fiber with a carboxyl content of 1.4mmol / g.
[0033] S2. Preparation of phenolic hydroxyl-rich nanofiber-based detection materials: Add 1.0 g of carboxylated nanocellulose fibers to a conical flask, then add 300 mL of deionized water, and ultrasonicate for 10 minutes to make it evenly dispersed; then add 1.0 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1.0 g of N-hydroxysuccinimide in sequence, and then add 2.0 g of polyethyleneimine, mix well, and stir at room temperature for 24 hours. After the reaction is completed, the product is centrifuged, the supernatant is removed, and the precipitate is repeatedly washed with deionized water until the washing liquid is neutral. The obtained product is amino-modified nanocellulose fiber; the amino-modified nanocellulose fiber obtained above is mixed with 300mL of deionized water, ultrasonicated for 10 minutes to make it uniformly dispersed, and then 1.0g of gallic acid is added, and then 1.0g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1.0g of N-hydroxysuccinimide are added in sequence, mixed evenly, and stirred at room temperature for 24h. After the reaction is completed, the product is centrifuged, the supernatant is removed, and the precipitate is repeatedly washed with deionized water until the washing liquid is neutral. The obtained product is a phenolic hydroxyl-rich nanofiber-based detection material, which is sensitive to Fe 3+ The minimum detection limit can be as low as 10 -10 mol / L.
[0034] S3. Preparation of recursive nanofiber-based detection material: 10 mg of phenolic hydroxyl-rich nanofiber-based detection material was uniformly dispersed in 100 mL of aqueous solution to prepare a 0.1 mg / mL phenolic hydroxyl-rich nanofiber-based detection material stock solution. 3+ After the aqueous solutions were mixed in a volume ratio of 1:5, the ultraviolet absorption intensity of the mixed solution at 196 nm was tested at room temperature, and the Fe 3+ Enrichment; at the same time, Fe 3+ It is enriched on the surface of phenolic hydroxyl-rich nanofiber-based detection materials, and a recursive nanofiber-based detection material is prepared in situ, which can further detect butyrylcholinesterase.
[0035] S4. Preparation of near-infrared responsive nanofiber-based photothermal effect materials: Add 20 μL of 50 mmol / L substrate iodide butylthiocholine iodide BuTCh solution to 20 μL of a 96-well plate at a concentration of 4000-16000 UL -1 The samples were incubated at 37°C for 30 min. Then, 0.01 g of the recursive nanofiber-based detection material was placed in the above solution and incubated for another 10 min. Finally, 20 μL of 5 mmol / L K 3 [Fe(CN) 6 ] solution and 60 μL of 10 mmol / L acetic acid-sodium acetate buffer (pH=5.0) were uniformly mixed with the solution in the above-mentioned well plate and incubated for 15 min to in situ generate Prussian blue nanoparticles on the surface of the recursive nanofiber-based detection material to prepare a near-infrared responsive nanofiber-based photothermal effect material.
[0036] The phenolic hydroxyl-rich nanofiber-based detection material prepared in Example 1 was used to detect Fe 3+ :Place Fe(NO 3 ) 3 (40.4 mg) was dissolved in 100 mL of deionized water to prepare 10 -3 mol / L Fe 3+ aqueous solution, and then the concentration of 10 -3 mol / LFe 3+ The aqueous solution was diluted to 10 -4 ~10 -11 0.01 g of phenolic hydroxyl-rich nanofiber-based detection material was loaded into the adsorption column, and then 1 L of Fe with different concentrations was added within 10 min. 3+ The aqueous solution passes through the adsorption column and the color change is recorded. 3+ The concentration of aqueous solution is 10-11 mol / L, the material still showed its original light yellow color; further Fe 3+ The concentration of the aqueous solution was increased to 10 -10 mol / L, the material changes from light yellow to light purple; as Fe 3+ The concentration of the aqueous solution ranged from 10 -10 mol / L increased to 10 -4 mol / L, the light purple color of the material gradually deepened to dark purple. Therefore, it can be explained that the phenolic hydroxyl-rich nanofiber-based detection material prepared in Example 1 has a good effect on Fe 3+ The minimum detection limit can be 10 -10 mol / L.
[0037] The recursive nanofiber-based detection material prepared in Example 1 was used to recursively detect the activity of butyrylcholine ester: first, 16000 UL -1 Butyrylcholinesterase BuChE solution, and then the concentration of 16000UL -1 The butyrylcholinesterase solution was diluted to 4000 to 15000 UL -1 . Add 20 μL of 50 mmol / L iodide butylthiocholine iodide BuTCh solution to 20 μL of 4000-16000 UL in a 96-well plate. -1 10 μL of 5 mmol / L K 3 [Fe(CN) 6 ] solution and 60 μL of 10 mmol / L acetic acid-sodium acetate buffer (pH = 5.0) were uniformly mixed with the solution in the above well plate and incubated for 15 min to generate Prussian blue nanoparticles in situ on the surface of the recursive nanofiber-based detection material to prepare a near-infrared responsive nanofiber-based photothermal effect material. During the detection process, ultrapure water was used as a blank control group. When the 808 nm near-infrared laser (1.0 W / cm 2 ) After irradiation for 3 minutes, the temperature of ultrapure water changes to 5.3±0.5℃; when the concentration of butyrylcholinesterase solution is 4000UL -1 When using 808nm near-infrared laser (1.0W / cm 2 ) After irradiation for 3 minutes, the temperature changed to 5.5°C, which was consistent with the results of the ultrapure water group; the concentration of butyrylcholinesterase solution was increased to 5000UL -1 , using 808nm near-infrared laser (1.0 W / cm 2) After irradiation for 3 minutes, the temperature changes to 8.4°C; the concentration of butyrylcholinesterase solution is increased to 6000UL -1 , using 808nm near-infrared laser (1.0W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 11.1°C; the concentration of butyrylcholinesterase solution is increased to 8000UL -1 , using 808nm near-infrared laser (1.0W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 16.4°C; the concentration of butyrylcholinesterase solution is increased to 10000UL -1 , using 808nm near-infrared laser (1.0W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 22.3°C; the concentration of butyrylcholinesterase solution is increased to 12000UL -1 , using 808 nm near-infrared laser (1.0 W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 24.8°C; the concentration of butyrylcholinesterase solution is increased to 14000UL -1 , using 808nm near-infrared laser (1.0W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 25.8°C; the concentration of butyrylcholinesterase solution is increased to 15000UL -1 , using 808nm near-infrared laser (1.0W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 26.1°C; the concentration of butyrylcholinesterase solution is increased to 16000UL -1 , using 808 nm near-infrared laser (1.0 W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 26.2°C. It can be obtained that the minimum detection limit of the recursive nanofiber-based detection material prepared in Example 1 for butyrylcholinesterase activity is 5000 to 15000 UL -1 .
[0038] S5. Preparation of nanofiber-based multifunctional hydrogel: First, 600 mg of doxorubicin, 100 mg of near-infrared responsive nanofiber-based photothermal responsive material and 120 mL of a 25 g / L water-soluble chitosan aqueous solution were mixed evenly, and then 15 mL of sodium alginate with a concentration of 1 g / L was added to cross-link the above substances into a hydrogel to prepare a nanofiber-based multifunctional hydrogel with a doxorubicin loading of 600 mg / g. 0.1 g of nanofiber-based multifunctional hydrogel was added to a conical flask containing 20 mL of phosphate buffer solution and placed in a constant temperature water bath shaker at 37 ° C. At the same time interval, 5.0 mL of solution was taken out from the conical flask and 5.0 mL of new phosphate buffer solution was added. The entire sampling time lasted for 48 hours. Then the doxorubicin release concentration of 480 nm wavelength in the solution was detected by ultraviolet spectrophotometer. The doxorubicin release rate of the nanofiber-based multifunctional hydrogel prepared in this embodiment 1 was 50% at 24 h, and the sustained release rate at 48 h was 95%.
[0039] The nanofiber-based multifunctional hydrogel prepared in Example 1 was used for in vivo tumor treatment: 100 μL of human breast cancer cells (McF-7) in phosphate buffered saline solution (concentration of 5×10 8 The weight and tumor growth of the mice were monitored daily with a vernier caliper for further treatment. After about 12 days, when the tumor length of the mice reached about 5 mm, the treatment experiment was performed. To evaluate the efficacy of combined photothermal and chemotherapeutic treatment, BALB / C mice bearing tumors were subcutaneously injected with 200 μL of the nanofiber-based multifunctional hydrogel prepared in Example 1. After 30 minutes, the mice were illuminated with an 808 nm laser (1.0 W / cm -1 , 30min) local irradiation mice. During the treatment process, the thermal image of the tumor was captured. The body weight and tumor mass of the mice before and after irradiation were measured to evaluate the therapeutic effect and toxicity, and the monitoring was continued for 12 days. After 12 days of treatment, the mass of the tumor of BALB / C nude mice decreased from 0.73g to 0.12g, proving that the nanofiber-based multifunctional hydrogel prepared in Example 1 has excellent in vivo tumor treatment performance.
[0040] Example 2
[0041] S1. Preparation of carboxylated nanocellulose fibers: Add 2.0g of bleached bagasse pulp fibers (absolutely dry pulp) to 200mL of deionized water and stir thoroughly until the cellulose is evenly dispersed in the water. Add 0.032g of TEMPO (0.1 mmol / g), 2.0g of NaBr (1mmol / g), and then 3.55mL of NaClO (6mmol / g) in sequence. Then, magnetic stirring was performed at room temperature for 4h, and the pH of the reaction system was adjusted to 10 with 0.5M NaOH until the pH value of the reaction system remained unchanged, which was the end point of the reaction. Add 5mL of anhydrous ethanol to terminate the reaction. Centrifuge the product, wash it repeatedly with distilled water until the supernatant is neutral, and freeze-dry it. The resulting product is carboxylated nanocellulose with a carboxyl content of 1.4mmol / g.
[0042] S2. Preparation of phenolic hydroxyl-rich nanofiber-based detection materials: Add 1.0 g of carboxylated nanocellulose fibers to a conical flask, then add 300 mL of deionized water, and ultrasonicate for 10 minutes to make it evenly dispersed; then add 1.0 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1.0 g of N-hydroxysuccinimide in sequence, and then add 2.0 g of polyethyleneimine, mix well, and stir at room temperature for 24 hours. After the reaction is completed, the product is centrifuged, the supernatant is removed, and the precipitate is repeatedly washed with deionized water until the washing liquid is neutral. The obtained product is amino-modified nanocellulose fiber; the amino-modified nanocellulose fiber obtained above is mixed with 300mL of deionized water, ultrasonicated for 10 minutes to make it uniformly dispersed, and then 1.0g of gallic acid is added, and then 1.0g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1.0g of N-hydroxysuccinimide are added in sequence, mixed evenly, and stirred at room temperature for 24h. After the reaction is completed, the product is centrifuged, the supernatant is removed, and the precipitate is repeatedly washed with deionized water until the washing liquid is neutral. The obtained product is a phenolic hydroxyl-rich nanofiber-based detection material, which is sensitive to Fe 3+ The minimum detection limit can be as low as 10 -10 mol / L, its effect on Fe 3+ The minimum detection limit can be 10 - 10 mol / L.
[0043] S3. Preparation of recursive nanofiber-based detection materials: 10 mg of phenolic hydroxyl-rich nanofiber-based detection materials were uniformly dispersed in 100 mL of aqueous solution to prepare a 0.1 mg / mL phenolic hydroxyl-rich nanofiber-based detection material stock solution. The above phenolic hydroxyl-rich nanofiber-based detection material stock solution and Fe3+ aqueous solutions of different concentrations were mixed in a volume ratio of 1:4, and the ultraviolet absorption intensity of the mixed solution at 196 nm was tested at room temperature to calculate the Fe3+ on the surface of the phenolic hydroxyl-rich nanofiber-based detection material. 3+ Enrichment, while Fe 3+ The phenolic hydroxyl-rich nanofiber-based detection material is enriched on its surface, and a recursive nanofiber-based detection material is prepared in situ, which can further detect butyrylcholinesterase.
[0044] S4. Preparation of near-infrared responsive nanofiber-based photothermal effect materials: Add 20 μL of 50 mmol / L substrate iodide butylthiocholine iodide BuTCh solution to 20 μL of a 96-well plate at a concentration of 4000-16000 UL -1 The samples were incubated at 37°C for 30 min. Then, 0.01 g of the recursive nanofiber-based detection material was placed in the above solution and incubated for another 10 min. Finally, 20 μL of 5 mmol / L K 3 [Fe(CN) 6 ] solution and 60 μL of 10 mmol / L acetic acid-sodium acetate buffer (pH=5.0) were uniformly mixed with the solution in the above-mentioned well plate and incubated for 15 min to in situ generate Prussian blue nanoparticles on the surface of the nanofibers to prepare near-infrared responsive nanofiber-based photothermal effect materials.
[0045] The phenolic hydroxyl-rich nanofiber-based detection material prepared in Example 2 was used to detect Fe 3+ :Place Fe(NO 3 ) 3 (40.4 mg) was dissolved in 100 mL of deionized water to prepare 10 -3 mol / L Fe 3+ aqueous solution, and then the concentration of 10 -3 mol / LFe 3+ The aqueous solution was diluted to 10 -4 ~10 -11 0.01 g of phenolic hydroxyl-rich nanofiber-based detection material was loaded into the adsorption column, and then 1 L of Fe3+ aqueous solution with different concentrations was passed through the adsorption column within 10 min, and the color change was recorded. 3+ The concentration of aqueous solution is 10 -11mol / L, the material still showed its original light yellow color; further Fe 3+ The concentration of the aqueous solution was increased to 10 -10 mol / L, the material changes from light yellow to light purple; as Fe 3+ The concentration of the aqueous solution ranged from 10 -10 mol / L increased to 10 -4 mol / L, the light purple color of the material gradually deepened to dark purple. Therefore, it can be explained that the phenolic hydroxyl-rich nanofiber-based detection material prepared in Example 1 has a good effect on Fe 3+ The minimum detection limit can be 10 -10 mol / L.
[0046] The recursive nanofiber-based detection material prepared in Example 2 was used to recursively detect the activity of butyrylcholine ester: First, 16000 UL -1 Butyrylcholinesterase BuChE solution, and then the concentration of 16000UL -1 The butyrylcholinesterase solution was diluted to 4000 to 15000 UL -1 . Add 20 μL of 50 mmol / L iodide butylthiocholine iodide BuTCh solution to 20 μL of 4000-16000 UL in a 96-well plate. -1 10 μL of 5 mmol / L K 3 [Fe(CN) 6 ] solution and 60 μL of 10 mmol / L acetic acid-sodium acetate buffer (pH = 5.0) were uniformly mixed with the solution in the above well plate and incubated for 15 min to generate Prussian blue nanoparticles in situ on the surface of the recursive nanofiber-based detection material to prepare a near-infrared responsive nanofiber-based photothermal effect material. During the detection process, ultrapure water was used as a blank control group. When the 808 nm near-infrared laser (1.0 W / cm 2 ) After irradiation for 3 minutes, the temperature of ultrapure water changes to 5.3±0.5℃; when the concentration of butyrylcholinesterase solution is 4000UL -1 When using 808nm near-infrared laser (1.0W / cm 2 ) After irradiation for 3 minutes, the temperature changed to 5.2°C, which was consistent with the results of the ultrapure water group; the concentration of butyrylcholinesterase solution was increased to 5000UL -1 , using 808nm near-infrared laser (1.0 W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 7.8°C; the concentration of butyrylcholinesterase solution is increased to 6000UL-1 , using 808nm near-infrared laser (1.0W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 10.3°C; the concentration of butyrylcholinesterase solution is increased to 8000UL -1 , using 808nm near-infrared laser (1.0W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 14.8°C; the concentration of butyrylcholinesterase solution is increased to 10000UL -1 , using 808nm near-infrared laser (1.0W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 18.9°C; the concentration of butyrylcholinesterase solution is increased to 12000UL -1 , using 808 nm near-infrared laser (1.0 W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 22.1°C; the concentration of butyrylcholinesterase solution is increased to 14000UL -1 , using 808nm near-infrared laser (1.0W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 22.5°C; the concentration of butyrylcholinesterase solution is increased to 15000UL -1 , using 808nm near-infrared laser (1.0W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 22.9°C; the concentration of butyrylcholinesterase solution is increased to 16000UL -1 , using 808 nm near-infrared laser (1.0 W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 23.0°C. It can be obtained that the minimum detection limit of the recursive nanofiber-based detection material prepared in Example 1 for butyrylcholinesterase activity is 5000 to 15000 UL -1 .
[0047] S5. Preparation of nanofiber-based multifunctional hydrogel: First, 500 mg of doxorubicin, 100 mg of near-infrared responsive nanofiber-based photothermal responsive material and 160 mL of 25 g / L water-soluble chitosan aqueous solution were mixed evenly, and then 20 mL of 1 g / L sodium alginate was added to cross-link the above substances into a hydrogel to prepare a nanofiber-based multifunctional hydrogel with a doxorubicin loading of 500 mg / g. 0.1 g of nanofiber-based multifunctional hydrogel was added to a conical flask containing 20 mL of phosphate buffer solution and placed in a constant temperature water bath shaker at 37 ° C. At the same time interval, 5.0 mL of solution was taken out from the conical flask and 5.0 mL of new phosphate buffer solution was added. The entire sampling time lasted for 48 hours. Then the doxorubicin release concentration at a wavelength of 480 nm in the solution was detected by a UV spectrophotometer. The nanofiber-based multifunctional hydrogel prepared in Example 2 had a doxorubicin release efficiency of 48.8% at 24 hours and a sustained release rate of 93.5% at 48 hours.
[0048] The nanofiber-based multifunctional hydrogel prepared in Example 2 was used for in vivo tumor treatment: 100 μL of human breast cancer cells (McF-7) in phosphate buffered saline solution (concentration of 5×10 8 The weight and tumor growth of the mice were monitored daily with a vernier caliper for further treatment. After about 12 days, when the tumor length of the mice reached about 5 mm, the treatment experiment was performed. To evaluate the efficacy of combined photothermal and chemotherapeutic treatment, BALB / C mice bearing tumors were subcutaneously injected with 200 μL of the nanofiber-based multifunctional hydrogel prepared in Example 2. After 30 minutes, the mice were illuminated with an 808 nm laser (1.0 W / cm -1 , 30min) local irradiation mice. During the treatment process, the thermal image of the tumor was captured. The body weight and tumor mass of the mice before and after irradiation were measured to evaluate the therapeutic effect and toxicity, and the monitoring was continued for 12 days. After 12 days of treatment, the mass of the tumor of BALB / C nude mice decreased from 0.82g to 0.15g, proving that the nanofiber-based multifunctional hydrogel prepared in Example 2 has excellent in vivo tumor treatment performance.
[0049] Example 3
[0050] S1. Preparation of carboxylated nanocellulose fibers: Add 2.0g of bleached bagasse pulp fibers (absolutely dry pulp) to 200mL of deionized water and stir thoroughly until the cellulose is evenly dispersed in the water. Add 0.032g of TEMPO (0.1mmol / g), 2.0g of NaBr (1mmol / g), and then add 3.55mL of NaClO (6mmol / g) in sequence. Then stir magnetically at room temperature for 4h, adjust the pH of the reaction system to 10 with 0.5M NaOH, until the pH value of the reaction system remains unchanged, which is the end point of the reaction. Add 5mL of anhydrous ethanol to terminate the reaction. Centrifuge the product, wash it repeatedly with distilled water until the supernatant is neutral, freeze-dry it, and the resulting product is carboxylated nanocellulose with a carboxyl content of 1.4mmol / g.
[0051] S2. Preparation of phenolic hydroxyl-rich nanofiber-based detection materials: Add 1.0 g of carboxylated nanocellulose fibers to a conical flask, then add 300 mL of deionized water, and ultrasonicate for 10 minutes to make it evenly dispersed; then add 1.0 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1.0 g of N-hydroxysuccinimide in sequence, and then add 2.0 g of polyethyleneimine, mix well, and stir at room temperature for 24 hours. After the reaction is completed, the product is centrifuged, the supernatant is removed, and the precipitate is repeatedly washed with deionized water until the washing liquid is neutral. The obtained product is amino-modified nanocellulose fiber; the amino-modified nanocellulose fiber obtained above is mixed with 300mL of deionized water, ultrasonicated for 10 minutes to make it uniformly dispersed, and then 1.0g of gallic acid is added, and then 1.0g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1.0g of N-hydroxysuccinimide are added in sequence, mixed evenly, and stirred at room temperature for 24h. After the reaction is completed, the product is centrifuged, the supernatant is removed, and the precipitate is repeatedly washed with deionized water until the washing liquid is neutral. The obtained product is a phenolic hydroxyl-rich nanofiber-based detection material, which is sensitive to Fe 3+ The minimum detection limit can be as low as 10 -10 mol / L, its effect on Fe 3+ The minimum detection limit can be 10 - 10 mol / L.
[0052] S3. Preparation of recursive nanofiber-based detection materials: 10 mg of phenolic hydroxyl-rich nanofiber-based detection materials were uniformly dispersed in 100 mL of aqueous solution to prepare a 0.1 mg / mL phenolic hydroxyl-rich nanofiber-based detection material stock solution. The above phenolic hydroxyl-rich nanofiber-based detection material stock solution and Fe3+ aqueous solutions of different concentrations were mixed at a volume ratio of 1:4, and the ultraviolet absorption intensity of the mixed solution at 196 nm was tested at room temperature to calculate the Fe3+ on the surface of the phenolic hydroxyl-rich nanofiber-based detection material. 3+ Enrichment, while Fe 3+ The phenolic hydroxyl-rich nanofiber-based detection material is enriched on its surface, and a recursive nanofiber-based detection material is prepared in situ, which can further detect butyrylcholinesterase.
[0053] S4. Preparation of near-infrared responsive nanofiber-based photothermal effect materials: Add 20 μL of 50 mmol / L substrate iodide butylthiocholine iodide BuTCh solution to 20 μL of a 96-well plate at a concentration of 4000-16000 UL -1 The samples were incubated at 37°C for 30 min. Then, 0.01 g of the recursive nanofiber-based detection material was placed in the above solution and incubated for another 10 min. Finally, 20 μL of 5 mmol / L K 3 [Fe(CN) 6 ] solution and 60 μL of 10 mmol / L acetic acid-sodium acetate buffer (pH=5.0) were uniformly mixed with the solution in the above-mentioned well plate and incubated for 15 min to in situ generate Prussian blue nanoparticles on the surface of the nanofibers to prepare near-infrared responsive nanofiber-based photothermal effect materials.
[0054] The phenolic hydroxyl-rich nanofiber-based detection material prepared in Example 3 was used to detect Fe 3+ :Place Fe(NO 3 ) 3 (40.4 mg) was dissolved in 100 mL of deionized water to prepare 10 -3 mol / L Fe 3+ aqueous solution, and then the concentration of 10 -3 mol / LFe 3+ The aqueous solution was diluted to 10 -4 ~10 -11 0.01 g of phenolic hydroxyl-rich nanofiber-based detection material was loaded into the adsorption column, and then 1 L of Fe3+ aqueous solution with different concentrations was passed through the adsorption column within 10 min, and the color change was recorded. 3+ The concentration of aqueous solution is 10 -11mol / L, the material still showed its original light yellow color; further Fe 3+ The concentration of the aqueous solution was increased to 10 -10 mol / L, the material changes from light yellow to light purple; as Fe 3+ The concentration of the aqueous solution ranged from 10 -10 mol / L increased to 10 -4 mol / L, the light purple color of the material gradually deepened to dark purple. Therefore, it can be explained that the phenolic hydroxyl-rich nanofiber-based detection material prepared in Example 1 has a good effect on Fe 3+ The minimum detection limit can be 10 -10 mol / L.
[0055] The recursive nanofiber-based detection material prepared in Example 3 was used to recursively detect the activity of butyrylcholine ester: First, 16000 UL -1 Butyrylcholinesterase BuChE solution, and then the concentration of 16000UL -1 The butyrylcholinesterase solution was diluted to 4000 to 15000 UL -1 . Add 20 μL of 50 mmol / L iodide butylthiocholine iodide BuTCh solution to 20 μL of 4000-16000 UL in a 96-well plate. -1 10 μL of 5 mmol / L K 3 [Fe(CN) 6 ] solution and 60 μL of 10 mmol / L acetic acid-sodium acetate buffer (pH = 5.0) were uniformly mixed with the solution in the above well plate and incubated for 15 min to generate Prussian blue nanoparticles in situ on the surface of the recursive nanofiber-based detection material to prepare a near-infrared responsive nanofiber-based photothermal effect material. During the detection process, ultrapure water was used as a blank control group. When the 808 nm near-infrared laser (1.0 W / cm 2 ) After irradiation for 3 minutes, the temperature of ultrapure water changes to 5.3±0.5℃; when the concentration of butyrylcholinesterase solution is 4000UL -1 When using 808nm near-infrared laser (1.0W / cm 2 ) After irradiation for 3 minutes, the temperature changed to 5.2°C, which was consistent with the results of the ultrapure water group; the concentration of butyrylcholinesterase solution was increased to 5000UL -1 , using 808nm near-infrared laser (1.0 W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 7.8°C; the concentration of butyrylcholinesterase solution is increased to 6000UL-1 , using 808nm near-infrared laser (1.0W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 10.3°C; the concentration of butyrylcholinesterase solution is increased to 8000UL -1 , using 808nm near-infrared laser (1.0W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 14.8°C; the concentration of butyrylcholinesterase solution is increased to 10000UL -1 , using 808nm near-infrared laser (1.0W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 18.9°C; the concentration of butyrylcholinesterase solution is increased to 12000UL -1 , using 808 nm near-infrared laser (1.0 W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 22.1°C; the concentration of butyrylcholinesterase solution is increased to 14000UL -1 , using 808nm near-infrared laser (1.0W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 22.5°C; the concentration of butyrylcholinesterase solution is increased to 15000UL -1 , using 808nm near-infrared laser (1.0W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 22.9°C; the concentration of butyrylcholinesterase solution is increased to 16000UL -1 , using 808 nm near-infrared laser (1.0 W / cm 2 ) After irradiation for 3 minutes, the temperature changes to 23.0°C. It can be obtained that the minimum detection limit of the recursive nanofiber-based detection material prepared in Example 1 for butyrylcholinesterase activity is 5000 to 15000 UL -1 .
[0056] S5. Preparation of nanofiber-based multifunctional hydrogel: First, 600 mg of hydrophobic drug camptothecin, 100 mg of near-infrared responsive nanofiber-based photothermal responsive material and 120 mL of 25 g / L water-soluble chitosan aqueous solution were mixed evenly, and then 15 mL of 1 g / L sodium alginate was added to cross-link the above substances into a hydrogel to prepare a nanofiber-based multifunctional hydrogel with a hydrophobic drug camptothecin loading of 600 mg / g. 0.1 g of nanofiber-based multifunctional hydrogel was added to a conical flask containing 20 mL of phosphate buffered ethanol solution and placed in a constant temperature water bath shaker at 37 ° C. At the same time interval, 5.0 mL of solution was taken out from the conical flask and 5.0 mL of new phosphate buffered ethanol solution was added. The entire sampling time lasted for 48 hours. Then the camptothecin release concentration at a wavelength of 254 nm in the solution was detected by a UV spectrophotometer. The camptothecin release efficiency of the nanofiber-based multifunctional hydrogel prepared in Example 3 was 30.4% in 24 hours, and the sustained release rate in 48 hours was 83.2%.
[0057] The nanofiber-based multifunctional hydrogel prepared in Example 3 was used for in vivo tumor treatment: 100 μL of human breast cancer cells (McF-7) in phosphate buffered saline solution (concentration of 5×10 8 The weight and tumor growth of the mice were monitored daily with a vernier caliper for further treatment. After about 12 days, when the tumor length of the mice reached about 5 mm, the treatment experiment was performed. To evaluate the efficacy of combined photothermal and chemotherapeutic treatment, BALB / C mice bearing tumors were subcutaneously injected with 200 μL of the nanofiber-based multifunctional hydrogel prepared in Example 3. After 30 minutes, the mice were illuminated with an 808 nm laser (1.0 W / cm -1 , 30min) local irradiation mice. During the treatment process, the thermal image of the tumor was captured. The body weight and tumor mass of the mice before and after irradiation were measured to evaluate the therapeutic effect and toxicity, and the monitoring was continued for 12 days. After 12 days of treatment, the mass of the tumor of BALB / C nude mice decreased from 0.81g to 0.23g, proving that the nanofiber-based multifunctional hydrogel prepared in Example 3 has excellent in vivo tumor treatment performance.
Claims
1. A method for preparing a nanofiber-based multifunctional hydrogel, characterized in that: The method comprises the following steps: S1. Preparation of carboxylated nanocellulose fibers: selectively oxidizing the hydroxyl groups on C2 and C3 of the cellulose structural unit of biomass pulp fibers into aldehyde groups using sodium periodate to prepare dialdehyde fibers; then oxidizing the aldehyde groups on C2 and C3 and the hydroxyl groups on C6 of the cellulose structural unit of the dialdehyde fibers into carboxyl groups using a TEMPO / NaBr / NaClO oxidation system, and regulating the degree of oxidation by controlling the reaction conditions to prepare carboxylated nanocellulose fibers; the biomass pulp fibers are bleached pulp fibers, and the bleached pulp fibers are a mixture of one or more of bleached bagasse pulp fibers, bleached coniferous wood pulp fibers, and bleached hardwood wood pulp fibers; S2. Preparation of phenolic hydroxyl-rich nanofiber-based detection materials: Using carboxylated nanocellulose fibers as a matrix, polyethyleneimine was introduced through an amidation reaction to prepare amino-modified nanocellulose fibers, and then the amino groups were reacted with the carboxyl groups of gallic acid to introduce phenolic hydroxyl groups to prepare phenolic hydroxyl-rich nanofiber-based detection materials; S3. Preparation of recursive nanofiber-based detection materials: Detection of Fe using phenolic hydroxyl-rich nanofiber-based detection materials 3+ , to achieve low concentration Fe 3+ Selective detection of Fe 3+ The phenolic hydroxyl-rich nanofiber-based detection material is enriched on its surface, and a recursive nanofiber-based detection material is prepared in situ, which can further detect the activity of butyrylcholinesterase; S4. Preparation of near-infrared responsive nanofiber-based photothermal effect materials: Using thiocholine iodide, the enzymatic hydrolysis product of butyrylcholinesterase, thiocholine, enriched on the surface of the recursive nanofiber-based detection material, 3+ Reduction to Fe 2+ , and then react with potassium ferrocyanide solution under acidic conditions to in-situ generate Prussian blue nanoparticles on the surface of the recursive nanofiber-based detection material. The Prussian blue nanoparticles have high absorption in the near-infrared light region, thereby obtaining a nanofiber-based photothermal effect material with near-infrared response; S5. Preparation of nanofiber-based multifunctional hydrogel: Near-infrared responsive nanofiber-based photothermal effect materials, tumor therapeutic drugs, and water-soluble chitosan are uniformly dispersed in water, and then sodium alginate is added under stirring at room temperature to form a nanofiber-based multifunctional hydrogel.
2. The preparation method according to claim 1, characterized in that: The preparation of carboxylated nanocellulose fibers in step S1 is specifically performed as follows: adding biomass pulp fibers to water, stirring thoroughly until cellulose is evenly dispersed in the water, adding TEMPO, NaBr, and NaClO in order, stirring at room temperature, adjusting the pH of the reaction system to 10 with NaOH, until the pH value of the reaction system remains unchanged, which is the end point of the reaction, adding anhydrous ethanol to terminate the reaction, centrifuging the product, washing until the supernatant is neutral, and freeze-drying, the resulting product is carboxylated nanocellulose fibers with a carboxyl content of 1.4 mmol / g; the addition ratio of the biomass pulp fibers, TEMPO, NaBr, and NaClO is 2.0~8.0 g: 0.032~0.128 g: 2.0~8.0 g: 3.55~14.20 mL; the corresponding TEMPO concentration is 0.1~0.4 mmol / g, the NaBr concentration is 1~4 mmol / g, and the NaClO concentration is 6~24 mmol / g.
3. The preparation method according to claim 1, characterized in that: The specific operation of preparing the phenolic hydroxyl-rich nanofiber-based detection material in step S2 is as follows: adding water to the carboxylated nanocellulose fiber, ultrasonically dispersing it uniformly, then adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide in sequence, then adding polyethyleneimine, mixing evenly, stirring at room temperature for reaction, after the reaction is completed, centrifuging the product, removing the supernatant, repeatedly washing the precipitate with deionized water until the washing liquid is neutral, and the resulting product is amino-modified nanocellulose fiber; mixing the obtained amino-modified nanocellulose fiber with water, ultrasonically dispersing it uniformly, then adding gallic acid, then adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide in sequence, mixing evenly, stirring at room temperature for reaction, after the reaction is completed, centrifuging the product, removing the supernatant, repeatedly washing the precipitate with deionized water until the washing liquid is neutral, and the resulting product is a phenolic hydroxyl-rich nanofiber-based detection material, which has a high sensitivity to Fe 3+ The minimum detection limit can be as low as 10 -10 mol / L, achieving the goal of Fe 3+ Trace detection; the added amount ratio of the carboxylated nanocellulose fiber, polyethyleneimine, and gallic acid is 1.0~5.0 g: 2.0~10.0 g: 1.0~5.0 g.
4. The preparation method according to claim 1, characterized in that: The specific operation of preparing the recursive nanofiber-based detection material in step S3 is: uniformly dispersing the phenolic hydroxyl-rich nanofiber-based detection material in water, preparing a 0.1 mg / mL phenolic hydroxyl-rich nanofiber-based detection material stock solution, mixing the phenolic hydroxyl-rich nanofiber-based detection material stock solution with different concentrations of Fe 3+ After the aqueous solutions were mixed in a volume ratio of 1:5 to 5:1, the ultraviolet absorption intensity of the mixed solution at 196 nm was tested at room temperature, and the Fe 3+ The enrichment amount was used to prepare the recursive nanofiber-based detection material in situ, which can further detect the activity of butyrylcholinesterase and control the different Fe 3+ The concentration of aqueous solution can regulate the Fe on the surface of phenolic hydroxyl-rich nanofiber-based detection materials 3+ The enrichment amount can be adjusted to adjust the detection limit of butyrylcholinesterase activity.
5. The preparation method according to claim 1, characterized in that: The specific operation of preparing the near-infrared responsive nanofiber-based photothermal effect material in step S4 is as follows: 20-40 μL of a 50-100 mmol / L substrate iodide butylthiocholine iodide BuTCh solution is added to 20-40 μL of a 4000-16000 UL solution in a 96-well plate. –1 The plate was incubated at 37°C for 30 min in a butyrylcholinesterase BuChE solution, and then 0.01-0.02 g of a recursive nanofiber-based detection material was added and incubated for another 10 min. Finally, 20-40 μL of a 5-10 mmol / L K3[Fe(CN)6] solution and 60-120 μL of a 10-20 mmol / L acetic acid-sodium acetate buffer were mixed evenly with the solution in the well plate and incubated for 15 min. Prussian blue nanoparticles were in situ generated on the surface of the recursive nanofiber-based detection material to prepare a near-infrared responsive nanofiber-based photothermal effect material. The material was irradiated with an 808 nm near-infrared laser for 3 min, and then the temperature change was recorded. The activity of butyrylcholinesterase was judged by the temperature change. The higher the near-infrared response temperature, the higher the butyrylcholinesterase activity.
6. The preparation method according to claim 1, characterized in that: The specific operation of preparing the nanofiber-based multifunctional hydrogel in step S5 is: uniformly dispersing the near-infrared responsive nanofiber-based photothermal effect material, tumor therapeutic drug and water-soluble chitosan in water, and then adding sodium alginate under stirring at room temperature to obtain the nanofiber-based multifunctional hydrogel; wherein the mass percentages of the near-infrared responsive nanofiber-based photothermal effect material, water-soluble chitosan, sodium alginate and tumor therapeutic drug in the hydrogel are 0.1~1 wt%, 0.1~2 wt%, 0.001~0.01 wt% and 0.05~1 wt%, respectively; and the tumor therapeutic drug is a mixture of one or more of doxorubicin, curcumin, moxifloxacin, vemurafenib and camptothecin.
7. The nanofiber-based multifunctional hydrogel prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the nanofiber-based multifunctional hydrogel prepared by the preparation method according to any one of claims 1 to 6 in the delivery of anticancer drugs, wherein the drug loading of the nanofiber-based multifunctional hydrogel is controllable and the maximum drug loading can reach 600 mg / g, the drug sustained release rate within 24 hours is as high as 50%, and the drug sustained release rate within 48 hours is as high as 95%.
Citation Information
Patent Citations
Preparation method and application of biocompatible nano composite hydrogel
CN111228213A
Biomass-based cascade-type double-temperature / pH / near-infrared stimuli-responsive intelligent nanofibers and preparation method and application thereof
CN111335040A